2022
DOI: 10.20377/jfr-702
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational care in corona times: Practices of care in Swedish families during the pandemic

Abstract: Objective: This paper analyses intergenerational relationships in Sweden during the corona pandemic, with a special focus on practices of care. The research question is: How is care between generations – between grandparents, adult children and grandchildren – done during pandemic conditions? Background: In Sweden, where an extensive welfare state provides affordable child- and eldercare, the corona strategy of generational separation has still affected family practices of care between generations. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
(61 reference statements)
0
8
0
1
Order By: Relevance
“…However, this study did not capture the nuances in the character of the care engagements of the genders. Our interviews with grandchildren, and also with adult children and grandparents (Eldén et al, 2021), describe grandmothers as more often having an overarching responsibility for organising care situations, doing more of the encompassing and often invisible sentient activities of care (Mason, 1996), while grandfathers are more often described as ‘fun playmates’. In the light of the general increased importance of grandparents in creating work-family balance for their adult children’s families, more studies paying attention to gendered differences in grandparental care practices are needed, as otherwise, the invisibility of gendered care work, in this case grandmother care, risks to be obscured.…”
Section: Discussion: Proximity Gender and Sentient Activities Of Carementioning
confidence: 97%
“…However, this study did not capture the nuances in the character of the care engagements of the genders. Our interviews with grandchildren, and also with adult children and grandparents (Eldén et al, 2021), describe grandmothers as more often having an overarching responsibility for organising care situations, doing more of the encompassing and often invisible sentient activities of care (Mason, 1996), while grandfathers are more often described as ‘fun playmates’. In the light of the general increased importance of grandparents in creating work-family balance for their adult children’s families, more studies paying attention to gendered differences in grandparental care practices are needed, as otherwise, the invisibility of gendered care work, in this case grandmother care, risks to be obscured.…”
Section: Discussion: Proximity Gender and Sentient Activities Of Carementioning
confidence: 97%
“…Grandparents' support and extended family collaboration took on increased importance in critical situations during the pandemic (Eldén et al, 2022). The Hong couple recounted how they relied on both sets of grandparents to get through the health and childcare crisis.…”
Section: Extended Family Collaboration In Childcarementioning
confidence: 99%
“…by limiting physical contact) (Del Boca et al, 2020; Stokes and Patterson, 2020). Only a few studies (Cantillon et al, 2021; Eldén et al, 2022; Lee et al, 2020; Mazzucchelli et al, 2020; Salin et al, 2020) have noted that grandparents provided childcare assistance or financial support for parents in emergency situations. For example, Cantillon et al (2021) found that grandparents in South Africa cared for children who were not living with their parents or whose parents had returned to work.…”
Section: Childcare and The Covid-19 Pandemicmentioning
confidence: 99%
See 2 more Smart Citations